Antibacterial potential of flavonoids with different hydroxylation patterns - Resende, Flávia Aparecida; Nogueira, Leonardo Gorla; Bauab, Tais Maria; Vilegas, Wagner; Varanda, Eliana Aparecida (Eclética Química, 2016)
The antibacterial activity of ten flavonoids, with variations in the hydroxylation pattern, was assayed in this study with the aim of investigating the influence of the hydroxyl groups of flavonoids on the evaluated activity. The evaluated degree of hydroxylation of the flavonoid molecules appears to have a crucial role in antibacterial effects. Kaempferol, the most active compound against Staphylococcus aureus, has a hydroxyl group in the B ring, a double bond between carbons 2 and 3 in conjunction with a 4-carbonyl group and hydroxyl groups at positions 3, 5 and 7, showing that the hydrophilic / lipophilic balance appears to be an important variable for antibacterial activity. With respect to the strain of Escherichia coli, the compounds evaluated did not inhibit completely bacterial growth; however they reduced the percentage of Gram-negative cells, under the conditions used in this work. These studies contribute to clarify the mechanisms by which these compounds act in the evaluated activity, since flavonoids can act through different mechanisms other than conventional antibiotics and could, therefore, be of use in the treatment of resistant bacteria.